Neither appendicitis nor sigmoiditis; it is an appendagitis - Abbas, Riyad (International Surgery Journal, 2022)
Appendagitis is defined as the inflammation of an omental appendix; it is a rare and often unrecognized cause of abdominal pain. Clinically, appendicitis simulates appendicitis or sigmoiditis; the evolution of radiology and in particular CT scans has facilitated the diagnosis and thus avoided hospitalization or even more unnecessary surgery. The treatment is conservative and relies on non-steroidal anti-inflammatory drugs and analgesics. The evolution is often favorable within 5 days of treatment on average. In reporting this clinical case, we tried to elucidate the diagnostic difficulty of this entity and to bring to light its different aspects through a brief review of the literature.